Trust Sebagai Pemoderasi Atas Anteseden Terhadap Voluntary Tax Compliance Studi Pada Wajib Pajak Kantor Pelayanan Pajak Pratama Depok Cimanggis - Sri Mulatsih; Suratno Suratno; Darmansyah Darmansyah (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The aim of this research is to know the effect of the demographic factors (age, education, the gross income, economic condision and taxpayer religiouity), self assessment system, and consultation Account Representative toward voluntary tax compliance and also to know trust in authorities is a variable that moderate the effect of the demographic factors, self assessment system, and consultation Account Representative against the voluntary tax compliance in Depok Cimanggis Small Tax Office. The Data were obtained by using quetionnaires to 100 respondents in Depok Cimanggis Small Tax Office. Data analysis using multiple regression analysis and Moderated Regression Analysis with an absolute difference test approach. The result showed that the demographic factors, and self assessment system had significant influence on voluntary tax compliance. Meanwhile, consultation Account Representative didn’t have influence toward voluntary tax compliance in Depok Cimanggis Small Tax Office. Trust in authorities moderates the influence of self assessment system toward voluntary tax compliance, but it doesn’t moderate the influence of the demographic factors and consultation Account Representative toward voluntary tax compliance in Depok Cimanggis Small Tax Office.